Analisis Kesulitan Belajar IPA Pada Siswa Kelas IV SD Negeri 064017 Medan Kec. Medan Perjuangan - Fitriyani, Romi; Ananda, Lala Jelita; Rangkuti, Irsan; Rozi, Fahrur; Manurung, Imelda Free Unita (Journal of Student Development Informatics Management (JoSDIM), 2023)
Thisresearchaimsto: (1) Determinethetypesofstudents' learningdifficulties in sciencesubjects in classIV of SD Negeri064017 Medanand (2) To describe the factors causing each student's learning difficulties in understanding science learning in grade IV SD Negeri064017 Medan. The population in this study was class IV students, totaling 24 students.  The data collection method used in this research is a questionnaire method with a research instrument in the form of the guttman scale.The analysis technique uses quantitative techniques which are calculated using percentages.  The results of this research show that the difficulty of learning science in class IV students at SD Negeri 064017 Medan is in the high category with a percentage of 57.83%.  With the percentage of alternative answers for each indicator, namely the interest indicator learning difficulty is 59.08%, the motivation indicator learning difficulty is 50.83%, the readiness indicator learning difficulty is 48.61%, the Physical indicator learning difficulty is 39.58%, the learning indicator is learning difficulty  family environment was 59.72%, learning difficulties were school environment indicators at 63.54%, and learning difficulties were community environment indicators at 89.58%.